Comparative study in swines' vocal cords healing after excision of fragment with CO2 laser with mitomycin and 5-fluorouracil postoperative topical application - Baptistella,Eduardo (2009)
PURPOSE: To evaluate the deposition of collagen fibers at pig's vocal folds after topical use of mitomycin or 5-fluorouracil, when partial exeresis of mucosa layer had been promoted by CO2 laser. METHODS: There were used 18 Larger white pigs which were anesthetized and submitted to mucosa fragment's exeresis, bilaterally, at its free border. The animals were divided into 3 groups, each one with 6 animals: control group, without topical drug application; mitomycin group; and 5-fluorouracil group. After 30 days, the animals were subjected to euthanasia, and samples of the vocal folds were collected and stained by picrosirius red technique with polarization for quantification of total collagen deposition. RESULTS: In control group, the mean rate of right vocal fold's collagen deposition at submucosa consisted in a 3428.66 micrometers area. There was found an area whose size had, in average, 2196.36 micrometers, in mitomycin group, and 2269.19 micrometers, in 5-fluorouracil group. CONCLUSION: Mitomycin and 5-fluorouracil had promoted beneficial change in vocal fold's cicatrization with less collagen deposition, but there was no significant statistically difference when they were compared between themselves.